PENGARUH STRES KERJA DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN - Tamin, Fadhlan Rizkiyanto; Armanu, Armanu (Jurnal Kewirausahaan dan Inovasi, 2023)
The objective of this research is to identify the effects of job stress and work discipline on the performance of BPS employees in Malang City. This explanatory research explains the causal relationships between variables through hypothesis testing. Using saturated sampling, all 31 employees of BPS of Malang City were selected as the respondents. The primary research data was harvested from Likert-scaled questionnaires, and the secondary was collected from books, past studies, online articles, official website, and documents related to the profile of the organization. This study employs multiple linear regression analysis, research instrument test, classical assumption test, and hypothesis testing. The results of the analysis indicate that the job stress among the employees of BPS of Malang City is low and that their work discipline is high. This research also finds that job stress has no significant effect on the employee performance and that work discipline significantly affects the employee performance. Furthermore, job stress and work discipline simultaneously have significant effect on the employee performance.